Species Gastropoda di Rawa Nipah Korong Gantiang Tangah Padang Kecamatan Ulakan Tapakis Kabupaten Padang Pariaman - Febri Yanti; Rezha Marvina; Ismed Wahidi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Nypa sp. grouped into mangrove forest plants as habitat for the Gastropoda. Gastropoda in this region are taken indefinitely by the public for consumption andsale so that rhy can influence the presence of these animal species. Based on the problems raised, a study was conducted with the aim of finding out the species of Gastropoda found in Rawa Nipah and knowing the physical chemical factors of the water that can affect the life of a Gastropoda. This research was conducted in June 2019 using purposive sampling method. The result found 7 species of Gatropoda namely Vittina turrita I, Vittina turrita II, Neritodryas dubia, Nerita polita, Cerithidea cingulate, Cassidula aurisfelis, and Ellobium aurisjudae. The physical and chemical environmental factor of water in Rawa Nipah Korong Gantiang Tangah Padang still support the existence of Gastropoda.